2018
DOI: 10.1096/fj.201800058r
|View full text |Cite
|
Sign up to set email alerts
|

Mif ‐deficiency favors an atheroprotective autoantibody phenotype in atherosclerosis

Abstract: The inflammatory cytokine macrophage migration-inhibitory factor (MIF) promotes atherosclerosis via lesional monocyte and T-cell recruitment. B cells have emerged as important components in atherogenesis, but the interaction between MIF and B cells in atherogenesis is unknown. Here, we investigated the atherosclerotic phenotype of Mif-gene deletion in Apoe mice. Apoe Mif mice fed a Western diet exhibited strongly reduced atherosclerotic lesions in brachiocephalic artery (BC) and abdominal aorta compared with c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
38
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 23 publications
(42 citation statements)
references
References 56 publications
4
38
0
Order By: Relevance
“…Although abundantly expressed by B cells compared to other immune populations, MIF is downregulated in blood B cells from early MS patients. This downregulation links to the survival of autoreactive naive B cells, as seen in atherosclerotic mice and MS , and coincides with decreased CD74 and increased CXCR4 surface expression, as part of a tightly controlled regulation loop in B cells. The reciprocal expression of CD74 and CXCR4 was supported by the increased migration capacity of B cells toward CXCL12 after inhibition of CD74 .…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…Although abundantly expressed by B cells compared to other immune populations, MIF is downregulated in blood B cells from early MS patients. This downregulation links to the survival of autoreactive naive B cells, as seen in atherosclerotic mice and MS , and coincides with decreased CD74 and increased CXCR4 surface expression, as part of a tightly controlled regulation loop in B cells. The reciprocal expression of CD74 and CXCR4 was supported by the increased migration capacity of B cells toward CXCL12 after inhibition of CD74 .…”
Section: Discussionmentioning
confidence: 79%
“…Besides functioning as an MHC class II chaperone protein, CD74 also has an MHC class II‐independent role in B‐cell maturation . Interestingly, MIF is also a noncognate ligand for chemokine receptor CXCR4 , which probably cooperate with CD74 to regulate B‐cell development and function through MIF .…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, Mif blockade in mice results in a regression of plaque areas [ 29 ]. Furthermore, antibody inhibition and genetic deletion studies have revealed that MIF influences the promotion of atherosclerosis by enhancing macrophage and T cell recruitment [ 21 , 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…MIF/CXCR pathways are drivers in several human diseases. The MIF/CXCR4 signaling axis controls monocyte, T-cell, and B-cell infiltration in atherosclerosis and other inflammatory conditions (17,19). It also contributes to cancer metastasis, cardiac fibroblast survival, and eosinophil inflammation (20,21).…”
Section: Introductionmentioning
confidence: 99%